Influence of Tooth Brushing and Previous Dental Visits on Dental Caries Status among Saudi Arabian Children - Sreekanth Kumar Mallineni; Abdullah Alassaf; Basim Almulhim; Sara Alghamdi (MDPI AG, 2023)
Objective: To evaluate the dental caries status and its association with tooth brushing frequency and previous dental visits among Arabian children. Methods: Arabian school children attend a specialty pediatric dental clinic at Majmaah University, Saudi Arabia. Only children of Saudi origin with primary dentition were included in the study, and only one examiner was involved in the assessment and data collection. The parents of children completed a questionnaire to investigate possible explanatory variables for caries status, including tooth brushing frequency and previous dental visits. Dental caries were diagnosed according to the criteria recommended by the World Health Organization (2013). The comparison performed was based on sex, age, tooth brushing frequency, and previous dental visits. The descriptive statistics were carried out using SPSS (version 21.0) with a p-value of <0.05 significance. Results: The study involved 268 Saudi children with a mean age of 4.6 ± 1.1 years. The caries prevalence was 78.8%, and the mean dmft was 5.82 ± 4.48, while the overall mean scores for decayed, missing, and filled were 3.903 ± 3.69, 1.18 ± 1.69, and 0.73 ± 1.35, respectively. The mean dmft scores for the <3 years, 3.1-6 years, and >6 years old children were found to be 1.74, 6.58, and 4.58, respectively. Among the children, the females reported higher dmf scores (7.51 ± 4.18) compared to males (4.97 ± 4.39) with a statistically significant difference (p < 0.001). Fifty percent of the children had tooth brushing habits of once daily, followed by never (22.4%), twice daily (15.7%), and rarely (11.2%) brushed their teeth. Statistically significant correlations were found between the children's dental caries status, age, and dental visits, while sex and tooth brushing did not find a correlation. Conclusion: The prevalence of dental caries among Arabian preschool children was higher. Mandibular second molars were commonly affected by dental caries, while mandibular central incisors were less frequently affected. The child's age and frequency of dental checkups were positively related to the prevalence of dental caries.